Antioxidant Activity Ethanolic Extract of Kalakai Leaf (Stenochlaena Palustris (BURM.F) Bedd) From Central Kalimantan by DPPH Method - Rabiatul Adawiyah; Halida Suryadini; Atika Abrar; Husna Fauzia; Faradila Faradila (Indonesian Journal of Global Health Research, 2025)
The diseases triggered by free radicals in Indonesia are increasing. Free radicals can be neutralized by antioxidants. The main sources of antioxidants are plants or fruits. Kalakai (Stenochlaena palustris (Burm.f.) Bedd.) is one of the typical plants of Kalimantan known for its medicinal properties. The leaves of Kalakai contain compounds such as flavonoids, phenols, tannins, alkaloids, and saponins, which have antioxidant abilities. This research aims to determine the antioxidant activity of Kalakai leaf extract from Central Kalimantan against DPPH free radicals based on the IC50 value. Antioxidant activity was measured using the DPPH method and analyzed using UV-Vis spectrophotometry at a wavelength of 516.6 nm. The results showed that Kalakai leaf extract had moderate antioxidant activity with an IC50 value of 241.547 ppm, while vitamin C as a positive control had strong activity with an IC50 of 10.031 ppm. These findings indicate that Kalakai leaves, although less potent than vitamin C, may serve as a promising natural antioxidant source. The conclusions is kalakai leaf extract exhibits moderate antioxidant activity and holds potential for further development in natural antioxidant applications.